XDR TYPHOID: THE PROBLEM AND ITS SOLUTION - Khan, Ejaz Ahmed (Journal of Ayub Medical College Abbottabad, 2019)
Pakistan has unfortunately witnessed an epidemic of extensively drug resistant (XDR) typhoid arising from Hyderabad since November 2016 and accounting for almost 50% cases now. Reports of XDR typhoid cases are occurring in other parts of Pakistan as well. The issue is mainly fewer antibiotic options for treatment with expected poor outcome. Diagnostics and therapeutic options must include more informative, acceptable and "gold standard" test of blood culture with emphasis on development of more rapid, reliable and cheap tests. Treatment options have dwindled to only two!: Oral azithromycin and for suspected severe or complicated XDR typhoid fever patients carbapenems. On a national level awareness of the problem and immediate preventive and control measures should be instituted at all levels and every sector to control typhoid. Measures aimed at health education of the healthcare professional and public about water hygiene, sanitary disposal and food safety, vaccination is of paramount importance.